Arabidopsis MSL10 Has a Regulated Cell Death Signaling Activity That Is Separable from Its Mechanosensitive Ion Channel Activity . Issue 7 (22nd July 2014) - Veley, Kira M.; Maksaev, Grigory; Frick, Elizabeth M.; January, Emma; Kloepper, Sarah C.; Haswell, Elizabeth S.
Abstract : MscS-Like 10, a mechanosensitive ion channel from Arabidopsis, has two functions, each attributable to a different domain of the protein. The C-terminal domain, which is conserved among all MscS-Like ion channels, mediates tension-regulated ion flux. The plant-specific N-terminal domain is capable of inducing cell death, and its activity is negatively regulated by its phosphorylation. Abstract: Members of the MscS superfamily of mechanosensitive ion channels function as osmotic safety valves, releasing osmolytes under increased membrane tension. MscS homologs exhibit diverse topology and domain structure, and it has been proposed that the more complex members of the family might have novel regulatory mechanisms or molecular functions. Here, we present a study of MscS-Like (MSL)10 from Arabidopsis thaliana that supports these ideas. High-level expression of MSL10-GFP in Arabidopsis induced small stature, hydrogen peroxide accumulation, ectopic cell death, and reactive oxygen species- and cell death-associated gene expression. Phosphomimetic mutations in the MSL10 N-terminal domain prevented these phenotypes. The phosphorylation state of MSL10 also regulated its ability to induce cell death when transiently expressed in Nicotiana benthamiana leaves but did not affect subcellular localization, assembly, or channel behavior. Finally, the N-terminal domain of MSL10 was sufficient to induce cell death in tobacco, independent of phosphorylation state. We conclude that the plant-specific N-terminal domain of MSL10 is capable of inducing cell death, this activity is regulated by phosphorylation, and MSL10 has two separable activities—one as an ion channel and one as an inducer of cell death. These findings further our understanding of the evolution and significance of mechanosensitive ion channels.